Study of Cadmium Bioaccumulation in Perna viridis through Food Pathway and Its Decontamination - Octavin Exaudina; Wahyu Retno Prihatiningsih; Heny Suseno; Budiawan Budiawan (Department of Chemistry Faculty of Science and Technology Walisongo, 2021)
Seafood can be contaminated by heavy metals that contained in seawater and the source of food that marine biotas eats. Cadmium is one of the contaminants found in the marine environment. Bioaccumulation studies via foood pathway were complement previous studies through the seawater pathway. This study also made an effort to biologically decontaminate cadmium using acetic acid and citric acid. The experimental results showed the total bioaccumulation ability of Cd by Perna viridis was 74.01. Cd decontamination which accumulates in the Perna viridis decreases the level up to 21%